Physical and rheological properties of asphalt modified with SEBS/montmorillonite nanocomposite. (1st March 2016) - Zapién-Castillo, Samuel; Rivera-Armenta, José Luis; Chávez-Cinco, María Yolanda; Salazar-Cruz, Beatriz Adriana; Mendoza-Martínez, Ana María
Graphical abstract: Highlights: For first time a nanocomposite SEBS-montmorillonite is reported as asphalt modifier. High temperature storage stability of modified asphalt was enhanced. Modified asphalt reduces tendency of become brittle and rigid at low temperature. Small amounts of nanocomposites have a better effect in asphalt. Abstract: A nanocomposite obtained from SEBS (styrene-ethylene–butylene-styrene) block copolymer and montmorillonite nanoclay was prepared through a melt mixing technique for asphalt modification. Asphalt binder blends with 3%, 4% and 6% of SEBS/nanoclay modifier were obtained by means of a high shear mixer. It was revealed by X-ray diffraction analysis that the nanocomposite showed an exfoliated dispersion pattern. Conventional physical tests were performed on the final mixes, and their thermal storage stabilities, rheological behavior and morphologies were also evaluated. The modifier effect on the asphalt binder was shown as an enhancement on these properties and it actually lowered the phase segregation problem that occurred when modification was executed using just polymer. The overall results indicate that these properties can be related to a better field performance of the asphalt.